Lessons of World War II and Strategic Planning of the Big Three (1945–1949) - I. E. Magadeev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The paper examines how military and political leaders of the Soviet Union, the United States and Great Britain assessed in the ﬁrst post-war years and in the face of emerging bipolar world order the lessons of World War II, how the latter inﬂuenced their strategic planning and forecasts with the emergence of nuclear weapons. The author outlines the key features of this period (1945–1949), including still fresh memories of the unprecedented destruction and losses of the past war, the US ‘nuclear monopoly’, and the absence of a system for nuclear deterrence. The paper provides a systematic comparison of lessons from the past war, learnt by the Soviet, the US and British establishment, identiﬁes similarities and diﬀerences between them. The author concludes that WWII was perceived by the political and military leaders of that time as a model of the eventual ‘great war’ in the future, which almost certainly would be ‘total’ and ‘global’ in scope and would demand both thorough preparations during the peacetime and the militarization of civil life. Indeed, the experience of WWII had greatly inﬂuenced the strategic and operational planning in the USSR, the USA and Great Britain in 1945–1949. Moscow prepared to face the potential aggression on its Western borders or in the Far East in order to avoid the mistakes of 1941. In Washington the decisionmakers acknowledged the Soviet superiority in conventional weapons and didn’t exclude the possibility that the Soviet Army could quickly establish control over the Western Europe and that the US military would have to retake it in a ‘new Operation Overlord’. The pessimistic outlook of the ‘defense of the Rhine’ was also shared in London, and the British military planned to evacuate the troops to the British Isles (‘shadow of Dunkirk’) and to focus on strategic bombing of the USSR and its allies. Even the appearance of nuclear weapons, that would dramatically alter the strategic context in the following years, played a relatively minor role in 1945–1949. The author concludes that the shadow of World War II and its lessons had a long-lasting eﬀect on the post-war international relations.